Impact of desert dust storms, PM10 levels and daily temperature on mortality and emergency department visits due to stroke - Oktay, M. Murat; Al, Behcet; Boğan, Mustafa; Kul, Seval; Gümüşboğa, Hasan; Bayram, Hasan (Frontiers in Public Health, 2023)
Objective: It is known that the inhalation of air pollutants adversely affects human health. These air pollutants originated from natural sources such as desert storms or human activities including traffic, power generating, domestic heating, etc. This study aimed to investigate the impacts of desert dust storms, particulate matter ≤10μm (PM10) and daily maximum temperature (MT) on mortality and emergency department (ED) visits due to stroke in the city of Gaziantep, Southeast Turkey. Method: The data on mortality and ED visits due to stroke were retrospectively recruited from January 1, 2009, to March 31, 2014, in Gaziantep city centre. Results: PM10 levels did not affect ED visits or mortality due to stroke; however, MT increased both ED visits (adjusted odds ratio [OR]=1.002, 95 % confidence interval [CI]=1.001-1.003) and mortality (OR=1.006, 95% CI=0.997-1.014) due to stroke in women. The presence of desert storms increased ED visits due to stroke in the total population (OR=1.219, 95% CI= 1.199-1.240), and all subgroups. It was observed that desert dust storms did not have an increasing effect on mortality. Conclusion: Our findings suggest that MT and desert dust storms can induce morbidity and mortality due to stroke.